Effects of Coffee Consumption In Improving Hyperglicemia In Diabetes-Induced Mice - Hesti Riany (Talenta Publisher, 2019)
Diabetes mellitus (DM) is a chronic metabolic disease. It was caused by lack of insulin or cells cannot use insulin so that blood glucose becomes high (hyperglycemia). And it will cause other systemic diseases of the disease (metabolic syndrome) that can increase the factor of death. Coffee is one of the consumed plants that contain antioxidants and chlorogenic acid that have a role as antihyperglycemia. In other hand Jambi as one of the coffee producing regions (arabica, robust and liberica) in Sumatra and it has a potency as a coffee producer. In addition, people's habits in consuming coffee have the opportunity to be one solution in overcoming diabetes. This study aimed to determine the effect of hyperglycemia disease. The method was experimental with 5 treatments (metformin, arabica, robust, liberica and aquades) and 3 replications. Before threatments mice were injected with streptozotosin in order to be hyperglycemia, then mice with blood glucose ≥ 116 mg / dl were measured their blood glucose, weight and made the histology of the liver. Then the datas were analyzed using ANAVA. The results showed that Jambi coffee (arabica, robust and liberica) can lower blood glucose levels hyperglycemia mice until day 16. And the treatment with liberica coffee lowers hyperglycemia with the lowest glucose levels. While the histological features of mice liver showed lower cell degeneration especially in mice by coffee treatment, especially arabica coffee.